Allen Squires and scuba divers St. Philip's. - Squires, Allen; Squires, Pearl (1962)
Photograph of Broad Cove, St. Philip's. Slide labeled by Pearl Squires as “Al and frogmen down on point at St. Philip's Beach NF”